Depressed Skull Fracture: Outcome of Surgical Treatment - Hossain, M Zahed; Mondle, MS; Hoque, M Monzurul (TAJ: Journal of Teachers Association, 2009)
Elevation and repair of an open depressed skull fracture is often thought of as an emergency procedure. Common indications for emergency elevation of a depressed skull fracture have been dural tear, seizure, gross contamination or mass effect from bone or a sizable underlying intracerebral hematoma. Over a 18 months period 93 patients with depressed skull fracture were admitted in the Neurosurgery ward of Rajshahi Medical College Hospital (RMCH) from July 2007 to December 2008 among which 67 patients needed surgical treatment. In 7 patients fracture crossed the midline over the superior sagittal sinus. Pre-operative GCS (Glasgow Coma Scale) score ranged from 5-15. Focal neurological deficit were present in 28 cases. Operations done were elevation of depressed fragments, repair of dural tear and hemostasis of sinus injury by gel-foam. No sinus injury required repair. Complete neurological recovery occurred in 21 cases. No death was recorded. One patient developed postoperative meningitis and controlled by parenteral antibiotics. One patient developed major wound infection including osteomyelitis but not intracranial infection. This patient had skin loss which was later closed by rotation flap of scalp operation. Seven patients had minor wound infection. One patient developed pseudomeningocele. doi: 10.3329/taj.v21i2.3794 TAJ 2008; 21(2): 140-146